The Effect of Intangible Asset Value, Sustainable Growth Rate, Return on Equity, and Dividend Payout Ratio on Company Market Value - Zaymin, Haidarullah; Berakon, Izra (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2022)
Purpose: This study aims to examine and analyze the effect of intangible asset value, sustainable growth rate, return on equity, and dividend payout ratio on the company's market value with firm age, firm size, and industry classification as control variables. Methodology: The research sample this time is 20 manufacturing companies. The method used in this study is panel data regression with model feasibility testing, this study uses the Fixed Effect Model as the best model in the study. Findings: The test results before and after using the control variables found that the variable value of intangible assets and dividend payout ratio had a significant positive effect on the market value of the company. Meanwhile, the variables of sustainable growth rate and return on equity do not affect the company's market value both before and after using the control variable. Novelty: This study continues previous research by using a different population, adding independent and control variables and using the manufacturing sector.